The Emerging Challenges of Adopting BIM in the Construction Industry: Evidence from Sabah, Malaysia - Syed Jamaludin, Shariffah Zatil Hidayah; Ismail, Noor Akmal Adillah; Ibrahim, Irma Hanie; Japlun, Nuraqilla (Faculty of Business Management, 2022)
Building Information Modelling (BIM) is the cornerstone of digital transformation in the architecture, engineering, and construction (AEC) industry. Building Information Modelling (BIM) is critical in boosting the productivity and quality of a building not only during design and construction stages but also includes post completion’s maintenance period. However, the majority of project stakeholders are still having difficulties in adopting BIM into practice, especially in the Sabah Construction Industry. In addressing the issues, the research aim is hence will analyze the challenges of adopting BIM and examine the Sabah state governments’ strategies that have been implemented to address the issues. The list of fourteen (14) BIM challenges that cover cost, process, people, technology were derived from a comprehensive literature review and further investigated through the use of 212 questionnaires distributed using online platform. The respondents were architects, engineers, and quantity surveyors. It was revealed that among the top challenges highlighted are: people being comfortable with the conventional process, high software cost, as well as incompetent staff to operate the software. The Sabah state government has assisted with the implementation of BIM by offering standard guidelines and continuous financial support; however, the strategies provided by them were still not enough. The result of this study showed that the implementation of BIM in the construction project in Sabah is still below expectations. The awareness among construction players on how beneficial BIM is in assisting their daily project tasks should be further enhanced for better BIM implementation in the region. The outcomes of this study will hopefully provide some directions towards developing managerial strategies for the government to aggressively promote BIM practices among project stakeholders.